Indoor Occupancy Detection Using Ultrasonic And Carbon Dioxide Sensors For Resilient Building Design Against Climate Change - Elina Mohd Husini; Fadli Arabi; Yakubu Aminu Dodo; Zulai Jarmai Baba-Girei; Okafor Izuchukwu Christian (Solid State Technology, 2024)
Indexed by ERA